Dialkyl maleate hydrogenation catalyst and preparation method thereof

By introducing hydrophobic groups on the activated carbon support and loading sub-nano-scale precious metal clusters, the problems of uncontrollable and poor selectivity of existing palladium carbon catalysts during metal loading are solved, and efficient dialkyl maleate addition Preparation of hydrogen reaction and highly selective dialkyl succinate.

CN119488901AActive Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311028431.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-15
Publication Date
2025-02-21
Estimated Expiration
2043-08-15

AI Technical Summary

Technical Problem

The existing palladium carbon catalysts are uncontrollable during metal loading, have poor dispersion of precious metals, have low atomic utilization, and have poor catalyst selectivity, making it easy to produce non-target products.

Method used

By introducing hydrophobic groups on the activated carbon intermediate with hydrophilic groups, high-density hydrophilic groups are dispersed to form a modified activated carbon carrier, and the sub-nano-scale precious metal clusters are loaded to improve the dispersion and interaction strength of precious metals.

Benefits of technology

The particle size of precious metal particles is less than 2.0 nm, which significantly reduces the load of precious metals on the carbon support, improves the selective hydrogenation conversion of dialkyl maleate and the selectivity of dialkyl succinate, avoiding the Over-hydrogenation is used to generate non-target products and maintain stability over long-term reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488901A_ABST
    Figure CN119488901A_ABST
Patent Text Reader

Abstract

The invention discloses a dialkyl maleate hydrogenation catalyst and a preparation method thereof. The dialkyl maleate hydrogenation catalyst comprises modified activated carbon and precious metal active components, the modified activated carbon is activated carbon with hydrophilic groups dispersed by hydrophobic groups on the surface, and the size of precious metal particles is smaller than 2.0 nm. The noble metal particles of the catalyst are small in particle size, the loading capacity of the noble metal on the carbon carrier is remarkably reduced, the conversion rate of the dialkyl maleate is 100% in the selective hydrogenation process of the dialkyl maleate, and the selectivity of the dialkyl succinate is greater than 99.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrogenation catalyst preparation, and in particular to a catalyst for preparing dialkyl succinate by selective hydrogenation of dialkyl maleate and a preparation method thereof. Background Art

[0002] In the route of preparing 1,4-butanediol (BDO) by hydrogenation of maleic anhydride to produce γ-butyrolactone (GBL) and tetrahydrofuran (THF), the carbon-carbon double bond saturation section of dimethyl maleate is a strong exothermic reaction. In the gas phase reaction system, the excess heat can be taken away by increasing the hydrogen-ester ratio with a large amount of cold hydrogen to avoid catalyst sintering. CN101745396A and CN101747189A disclose a copper-zinc-aluminum catalyst for partial hydrogenation of dialkyl maleate to produce dialkyl succinate. The catalyst is composed of a main active component and an auxiliary agent, the main active component is copper oxide, and the auxiliary agents are aluminum oxide and zinc oxide. In the total weight of the catalyst, copper oxide accounts for 40% to 60%, zinc oxide accounts for 20% to 50%, and aluminum oxide accounts for 10% to 20%. The main problem is that the active metal component content is high, the temperature resistance is poor, and it needs to be carried out under high pressure conditions. The more important problem is that the catalyst selectivity is poor, and more hydrogenolysis products 1,4-butanediol, γ-butyrolactone, and tetrahydrofuran will be generated. The gas-liquid phase mixed reaction system is a two-stage hydrogenation. CN103946201B discloses a method for producing 1,4-butanediol by hydrogenating dialkyl maleate in a mixed liquid phase / gas phase. The first stage uses a supported transition metal catalyst with good double bond selectivity and high low-temperature reaction activity, and the second stage uses a Cu-based catalyst with high hydrogenolysis activity.

[0003] For the first stage hydrogenation process, the carrier component in the catalyst is generally selected from alumina, silicon oxide, titanium oxide, zirconium oxide, porous carbon materials, etc. The porous carbon materials have the advantages of good acid resistance, high mechanical strength, suitable pores, etc., and are compatible with the liquid phase hydrogenation reaction system of dimethyl maleate. The metal component is mainly selected from Group VIII metals Rh, Ru, Pd, Pt, etc., and non-precious metal elements such as Ni, Co, W, Mo, Cr, Cu, Au, B, Ga, P, Bi, etc. are often added as additives to improve the dispersion of precious metals and catalytic activity.

[0004] CN103464153A discloses a hydrogenation catalyst for producing dimethyl succinate and a preparation method thereof. The method uses a resin-based spherical activated carbon with a high specific surface area and a microporous structure as a carrier, loads palladium nitrate by a liquid phase sedimentation method, and then loads WO3 on it, and then washes, dries, and roasts to obtain a catalyst. The catalyst carrier resin-based activated carbon has a high cost, which hinders its industrial application.

[0005] CN111330581B discloses an acid-resistant hydrogenation catalyst for hydrogenating maleic acid to prepare succinic acid, wherein the carrier is one of activated carbon, α-alumina, silicon oxide or silicon carbide, and the active components of the catalyst are composed of two elements A and B, wherein A is one of Ni, Co, W, Mo, Rh, Cr, Ru, and Pd, and B is one of Cu, Pt, Au, B, Ga, P, and Bi. The catalyst is prepared by hydrophilizing the carrier using ozone, nitric acid, and hypochlorous acid (salt), wherein the contact angle between the carrier and water is less than 60°, and the particle size of the active metal component is 2 to 50 nanometers.

[0006] In summary, the catalyst for hydrogenation of precious metal palladium supported on carbon carrier for partial hydrogenation of maleic acid / dialkyl maleate to prepare succinic acid / dialkyl succinate generally adopts oxidation / hydrophilic treatment, which can improve the dispersion of precious metal to a certain extent and achieve a metal grain size of 2 to 50 nanometers. However, hydrophilic treatment cannot further reduce the size of palladium metal particles and the particle size distribution is uneven, so it is of great significance to develop a carbon-supported catalyst with smaller palladium metal particle size and high stability. Summary of the invention

[0007] In view of the problems of uncontrollable metal loading process, poor noble metal dispersion and low atomic utilization in the prior art palladium carbon catalyst, the present invention provides a dialkyl maleate hydrogenation catalyst and a preparation method thereof. The catalyst of the present invention has a small noble metal particle size, significantly reduces the loading amount of the noble metal on the carbon carrier, and is used in the process of selective hydrogenation of dialkyl maleate to achieve a dialkyl maleate conversion rate of 100% and a dialkyl succinate selectivity of more than 99.5%.

[0008] The inventor has found through research that the precursor adsorbed on the high-density hydrophilic surface is easy to aggregate during the reduction process, producing large metal particles, and the metal atoms in the inner layer of the large particles cannot play a catalytic role. The inventor has further found that on the basis of the activated carbon intermediate with hydrophilic groups, hydrophobic groups are introduced without reducing the number of hydrophilic groups, and the high-density hydrophilic groups are dispersed into small independent hydrophilic units. This spatial confinement effect is used to reduce the aggregation behavior of metal particles. By regulating the ratio of hydrophilic groups to hydrophobic groups and the types of hydrophobic groups, the noble metals have good dispersibility and interaction strength on the surface of the modified activated carbon carrier, thereby obtaining a catalyst with highly dispersed sub-nanometer noble metal clusters, so that the catalyst has high hydrogenation reaction activity at low metal loading, and the hydrophobic group promotes the rapid desorption of the reaction product dialkyl succinate from the reaction center to avoid excessive hydrogenation to generate non-target products. The catalyst has excellent reactivity, selectivity and stability for the selective hydrogenation reaction of dialkyl maleate.

[0009] The first aspect of the present invention provides a dialkyl maleate hydrogenation catalyst, comprising: modified activated carbon and a noble metal active component, wherein the modified activated carbon is activated carbon having hydrophilic groups dispersed by hydrophobic groups on the surface, and the size of the noble metal particles is less than 2.0 nm.

[0010] Further, the hydrophobic group is derived from a hydrophobic modifier, which is an organosilane substance, selected from at least one of vinyl trichlorosilane, phenyl dichlorosilane, chloromethyl triethoxysilane, vinyl triethoxysilane, vinyl triacetoxysilane, trimethoxysilane, trimethoxyvinyl silane, dimethoxymethyl vinyl silane, etc., preferably at least one of trimethoxysilane, vinyl triethoxysilane, trimethoxyvinyl silane, dimethoxymethyl vinyl silane, etc., more preferably at least one of trimethoxyvinyl silane, dimethoxymethyl vinyl silane, etc. The amount of the hydrophobic group is 0.1 to 1 mmol / g, preferably 0.1 to 0.6 mmol / g.

[0011] The ratio of the number of the hydrophobic groups to the number of the hydrophilic groups is 0.05 to 1:1, preferably 0.1 to 0.4:1.

[0012] Furthermore, the hydrophilic group is at least one of acidic hydrophilic groups such as carboxyl, phenolic hydroxyl or lactone. The amount of the hydrophilic group is not less than 0.3 mmol / g, preferably not less than 0.5 mmol / g, and more preferably 0.5 to 1.4 mmol / g.

[0013] Furthermore, the noble metal is at least one of palladium, ruthenium, rhodium, platinum, etc., preferably at least one of palladium and ruthenium, and more preferably palladium.

[0014] Furthermore, in the catalyst, the content of the precious metal as an element is 0.01% to 0.20%, preferably 0.02% to 0.10%, based on the weight of the catalyst.

[0015] Furthermore, in the catalyst, the size of the noble metal particles is preferably less than 1.0 nm, and more preferably 0.2 to 1.0 nm.

[0016] The second aspect of the present invention provides a method for preparing a dialkyl maleate hydrogenation catalyst, comprising:

[0017] (1) An oxidizing agent is mixed with activated carbon and treated at a temperature of 20 to 90° C. for 0.5 to 24 hours to obtain a modified activated carbon intermediate;

[0018] (2) The modified activated carbon intermediate obtained in step (1) is mixed and stirred with an alcohol solution of a hydrophobic modifier at 20 to 80° C. for 4 to 24 hours, filtered, washed, and dried to obtain modified activated carbon;

[0019] (3) Loading precious metal active components on the modified activated carbon obtained in step (2) to obtain the catalyst.

[0020] Furthermore, in step (1), the activated carbon source can be at least one of wood-based activated carbon, petroleum-based activated carbon, and coal-based activated carbon, wherein the wood-based activated carbon can be derived from at least one of coconut shell charcoal, fruit shell charcoal, and bamboo charcoal, preferably coconut shell charcoal. The specific surface area of ​​the activated carbon used is 300 to 2000 m 2 / g, preferably 500 to 1500 m 2 / g, an average pore diameter of 0.3 to 5.0 nm, preferably 0.8 to 3.5 nm, and an ash content of no more than 10 wt%, preferably no more than 7 wt%.

[0021] Furthermore, in step (1), when the ash content of the activated carbon used exceeds 10wt%, it can be pretreated to obtain activated carbon with an ash content not exceeding 10wt%. The pretreatment includes: at least one of water washing, alkali washing, acid washing, etc. Among them, water washing can be soaked in deionized water for 5 to 72 hours, and the liquid-to-solid volume ratio is 5 to 10 times. Alkali washing can be soaked in an alkaline solution, and the alkaline solution is selected from one or more aqueous solutions of ammonia, sodium hydroxide, potassium hydroxide, and lithium hydroxide, and the concentration of the alkaline solution is 0.5 to 1.5 mol / L, the liquid-to-solid volume ratio is 5 to 10:1, and the alkaline washing time is 3 to 24 hours. Acid washing can be soaked in an acid solution, and the acid solution is selected from one or more aqueous solutions of nitric acid, hydrochloric acid, and sulfuric acid, and the concentration of the acid solution is 0.5 to 1.5 mol / L, the liquid-to-solid volume ratio is 5 to 10:1, and the acid washing time is 3 to 24 hours.

[0022] Furthermore, in step (1), the oxidizing agent is selected from at least one of nitric acid, hydrogen peroxide, hypochlorous acid, sodium hypochlorite, perchloric acid, sodium perchlorate, ammonium persulfate, etc. The mass concentration of the oxidizing agent is 1% to 40%.

[0023] Furthermore, after the treatment in step (1), the modified activated carbon intermediate can be washed with deionized water after cooling to obtain the modified activated carbon intermediate. The surface of the modified activated carbon intermediate has at least one of the acidic hydrophilic groups such as carboxyl, phenolic hydroxyl or lactone. Preferably, the number of hydrophilic groups is not less than 0.3 mmol / g, preferably the number of hydrophilic groups is not less than 0.5 mmol / g, and more preferably 0.5 to 1.4 mmol / g.

[0024] Furthermore, in step (2), the alcohol used in the alcohol solution is a small molecule alcohol, the carbon number of the small molecule alcohol is C1-C6, and is preferably methanol. In the alcohol solution of the hydrophobic modifier, the mass content of the hydrophobic modifier is 1% to 80%, preferably 3% to 50%, and more preferably 5% to 20%.

[0025] Furthermore, in step (2), the hydrophobic modifier is an organosilane substance, selected from at least one of vinyltrichlorosilane, phenyldichlorosilane, chloromethyltriethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, trimethoxysilane, trimethoxyvinylsilane, dimethoxymethylvinylsilane, etc., preferably at least one of trimethoxysilane, vinyltriethoxysilane, trimethoxyvinylsilane, dimethoxymethylvinylsilane, etc., more preferably at least one of trimethoxyvinylsilane, dimethoxymethylvinylsilane, etc.

[0026] Furthermore, in step (2), the liquid-to-solid volume ratio of the alcohol solution of the hydrophobic modifier to the modified activated carbon intermediate obtained in step (1) is 3 to 10:1.

[0027] Furthermore, in step (2), the washing may be performed using a small molecule alcohol solvent, wherein the carbon number of the small molecule alcohol is C1-C6, and methanol is preferred.

[0028] Further, in step (2), the drying conditions are as follows: the drying temperature is 50-150°C, preferably 80-120°C, and the drying time is 1-24h, preferably 2-12h. The modified activated carbon obtained after drying, measured by Boehm titration method, shows that the number of acidic hydrophilic groups of the modified activated carbon intermediate before and after modification is basically unchanged, but the contact angle test proves that its hydrophilicity decreases. Further, in the modified activated carbon, the number of hydrophobic groups is 0.1-1mmol / g, preferably 0.1-0.6mmol / g.

[0029] Further, in step (3), the method of loading the noble metal active component is as follows: the modified activated carbon is mixed with water (preferably deionized water) 2 to 5 times (preferably 2.5 to 4 times) the saturated water absorption of the modified activated carbon, and the noble metal precursor solution is dripped into the obtained mixture under stirring conditions, and then the stirring is continued for more than 15 minutes, and then the mixture is allowed to stand (preferably the standing time is 4 to 24 hours), filtered, washed, and dried (50 to 120° C., preferably 80 to 100° C. for 2 to 10 hours) to obtain the catalyst. Wherein, the noble metal can be at least one of palladium, ruthenium, rhodium, platinum, etc., preferably at least one of palladium and ruthenium, and more preferably palladium. The noble metal precursor can be a conventional noble metal salt, and the mass concentration of the noble metal precursor solution is 0.5% to 5.0%, preferably 1.0% to 2.0%. Taking palladium as an example, it can be one or more of palladium nitrate, palladium chloride, tetraammine palladium nitrate, dichlorotetraammine palladium, palladium acetate, acetylacetonate palladium, etc. The present invention is described with palladium chloride as a representative, but is not limited thereto. The molar ratio of palladium chloride to hydrochloric acid is 1.5 to 3.0:1, preferably 1.8 to 2.2:1, and an aqueous solution of palladium chloride with a palladium mass fraction of 0.5% to 5.0%, preferably 1.0% to 2.0%, is prepared as an impregnation solution, and the pH value is 1 to 3, preferably 1.2 to 2.4. Among them, the saturated water absorption capacity V of the modified activated carbon is measured in ml / g. The temperature of the mixture of modified activated carbon and water is 20 to 50°C, preferably 25 to 35°C. The stirring speed of the stirring is 150 to 500rpm, preferably 200 to 400rpm. The washing can be done with deionized water.

[0030] Furthermore, the noble metal may be at least one of palladium, ruthenium, rhodium, platinum, etc., preferably at least one of palladium and ruthenium, and more preferably palladium.

[0031] Furthermore, in the catalyst, the content of the precious metal as an element is 0.01% to 0.20%, preferably 0.05% to 0.10%, based on the weight of the catalyst.

[0032] Furthermore, in the catalyst, the size of the noble metal particles is less than 2.0 nm, preferably less than 1.0 nm, and more preferably 0.2 to 1.0 nm.

[0033] Furthermore, the catalyst of the present invention needs to be reduced before use. The reducing gas can be hydrogen. The reducing conditions are as follows: the reducing temperature is 50-200°C, the reducing pressure is 0.1-2.0 MPa, and the hydrogen volume space velocity is 50-1000 h -1 , the reduction time is 5 to 24 hours. Preferably, the reduction temperature is 80 to 170°C, the reduction pressure is 0.5 to 1.5 MPa, and the hydrogen volume space velocity is 150 to 750 h -1 The reduction time is 8 to 12 hours.

[0034] The third aspect of the present invention provides the use of the above catalyst in the selective hydrogenation of dialkyl maleate to prepare dialkyl succinate.

[0035] Furthermore, the hydrogenation conditions are as follows: the selective hydrogenation of dialkyl maleate to prepare dialkyl succinate is evaluated in a fixed bed reaction evaluation device, and the mass percentage of dimethyl maleate in the raw material used is not less than 99.8%. After the reduction operation is completed, hydrogen and dimethyl maleate are contacted and reacted in the catalyst bed, and the reaction conditions are: the reaction temperature is 50 to 170°C, preferably 80 to 120°C, the pressure is 0.1 to 2.5 MPa, preferably 0.5 to 1.5 MPa, and the volume space velocity is 0.1 to 3 h -1 , preferably 0.2 to 2 hours -1 The molar ratio of hydrogen to ester is 3 to 100: 1, preferably 5 to 50: 1, and more preferably 5 to 20: 1. After the reaction, the mixture is analyzed by gas chromatography.

[0036] Compared with the prior art, the catalyst of the present invention has the following beneficial effects:

[0037] 1. The catalyst of the present invention uses modified activated carbon as a carrier and noble metal as an active metal component. The average particle size of the noble metal is less than 2 nanometers, which significantly reduces the loading amount of the noble metal on the carbon carrier. When used in the selective hydrogenation process of dialkyl maleate, the conversion rate of dialkyl maleate can reach 100%, and the selectivity of dialkyl succinate can reach more than 99.5%.

[0038] 2. In the preparation method of the catalyst of the present invention, the modified activated carbon is based on the activated carbon intermediate with hydrophilic groups, and hydrophobic groups are introduced without reducing the number of hydrophilic groups, and the high-density hydrophilic groups are separated into independent hydrophilic units. The aggregation behavior of metal particles is reduced by using this spatial confinement effect. By regulating the types and ratios of hydrophilic groups and hydrophobic groups, the noble metals have good dispersibility and interaction strength on the surface of the modified activated carbon carrier, thereby obtaining a catalyst with highly dispersed sub-nanometer noble metal clusters, so that the catalyst has high hydrogenation reaction activity at low metal loading, and the hydrophobic groups promote the desorption of the reaction product dialkyl succinate from the reaction center to avoid excessive hydrogenation to generate non-target products; in addition, in the long-cycle reaction process, the introduced hydrophobic groups play a role in dispersing palladium metal clusters to prevent them from aggregating to form large particles, and have better long-cycle operation stability. The metal utilization rate of the method of the present invention is much higher than that of the metal nanoparticle agglomerates prepared by conventional methods. The catalyst prepared by the method of the present invention has excellent reaction activity and dialkyl maleate selectivity in the selective hydrogenation reaction of dialkyl maleate, and the reaction activity does not decrease significantly after continuous and stable reaction for 2000 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a transmission electron microscope photograph of the catalyst in Example 3. DETAILED DESCRIPTION

[0040] The present invention will be further described below by way of examples, but the contents of the present invention are not limited thereto.

[0041] In the present invention, the particle size of the precious metal particles is analyzed using a TECNAIG2F20 transmission electron microscope (TEM) produced by FEI Company, with an operating voltage of 200 kV.

[0042] In the present invention, the specific surface area and average pore size are obtained by low temperature N2 physical adsorption and desorption test and calculated according to the BET adsorption theory model, and are measured using an ASAP 2420 automatic gas adsorption instrument produced by Micromeritics.

[0043] In the present invention, the non-hydrophilic group and the hydrophilic group are qualitatively and quantitatively analyzed for specific elements using X-ray fluorescence spectroscopy combined with Boehm chemical titration method.

[0044] Example 1

[0045] (1) Weigh 20 g of coconut shell activated carbon (the specific surface area of ​​activated carbon is 827 m 2 / g, with an average pore size of 1.99nm) in a beaker, soaked in 400mL of deionized water for 48h, and washed with 1200ml of deionized water until there is no mechanical impurities and it is clear and colorless, and then filtered; 200mL of 1mol / L NaOH solution was added to the activated carbon obtained by filtration, and the mixture was stirred for 4h and filtered, and the filtrate was washed with deionized water until it was close to neutral and filtered, and then 200mL of 1mol / L HCl solution was added, and the mixture was stirred for 4h and filtered, and the filtrate was washed with deionized water until it was close to neutral and filtered, and the activated carbon pretreatment was completed, and the ash content of the activated carbon after pretreatment was 2.8wt%;

[0046] (2) preparing 100 mL of 5% nitric acid aqueous solution, mixing 20 g of pretreated activated carbon therewith and refluxing at 80° C. for 4 h, cooling, washing with deionized water and filtering to obtain a modified activated carbon intermediate having a hydrophilic group number of 0.85 mmol / g;

[0047] (3) The modified activated carbon intermediate and a methanol solution of trimethoxyvinylsilane with a mass fraction of 20% were refluxed at 50°C for 8 hours, wherein the liquid-to-solid volume ratio of the alcohol solution of the hydrophobic modifier to the modified activated carbon intermediate was 5:1, and then filtered and washed with methanol, and dried in an oven at 80°C for later use, to obtain a modified activated carbon with a hydrophobic group number of 0.25 mmol / g;

[0048] (4) Prepare a palladium chloride precursor solution with a pH value of 1.2 and a concentration of 20 g / L, take 60 mL of deionized water and mix it with the modified activated carbon, stir at 30° C. and drop 8.3 g of the precursor solution, continue stirring for 30 min, let it stand and wash it with deionized water until it is neutral, place it in an oven at 100° C. and dry it for 12 h, and you can get a palladium carbon catalyst to be reduced with a palladium loading of 0.05% (mass fraction).

[0049] (5) The catalyst to be reduced is loaded into a fixed bed reactor and reduced with hydrogen at 1 MPa and 150°C for 8 h, with a hydrogen volume space velocity of 600 h -1 The obtained reduced palladium carbon catalyst was recorded as 0.05Pd / G1-AC.

[0050] Example 2

[0051] In Example 2, steps (1), (2) and (3) are the same as those in Example 1;

[0052] (4) Prepare a palladium chloride precursor solution with a pH value of 1.2 and a concentration of 20 g / L, take 60 mL of deionized water and mix it with the modified activated carbon, stir at 30° C. and drop 3.3 g of the precursor solution, continue stirring for 30 min, let it stand and wash it with deionized water until it is neutral, place it in an oven at 100° C. and dry it for 12 h, and you can get a palladium carbon catalyst to be reduced with a palladium loading of 0.02% (mass fraction).

[0053] (5) The reduction method of step (5) of Example 1 was used to finally obtain a reduced palladium carbon catalyst, which was recorded as 0.02Pd / G1-AC.

[0054] Example 3

[0055] In Example 3, step (1) is the same as in Example 1;

[0056] (2) preparing 100 mL of 20% nitric acid aqueous solution, mixing 20 g of pretreated activated carbon therewith and refluxing at 80° C. for 4 h, cooling, washing with deionized water and filtering to obtain a modified activated carbon intermediate having a hydrophilic group number of 1.25 mmol / g;

[0057] (3)-(5) The method of steps (3)-(5) of Example 1 was adopted to finally obtain a reduced palladium carbon catalyst recorded as 0.05Pd / G2-AC.

[0058] Example 4

[0059] In Example 4, steps (1) and (2) are the same as those in Example 1;

[0060] (3) The modified activated carbon intermediate and a methanol solution of 20% phenyldichlorosilane by mass were refluxed at 50°C for 8 hours, wherein the liquid-to-solid volume ratio of the alcohol solution of the hydrophobic modifier to the modified activated carbon intermediate was 5:1, and then filtered and washed with methanol, and dried in an oven at 80°C for later use, to obtain a modified activated carbon with a hydrophobic group number of 0.28 mmol / g;

[0061] (4)(5) The method of steps (4) and (5) of Example 1 was used to finally obtain a reduced palladium carbon catalyst, which was recorded as 0.05Pd / G3-AC.

[0062] Example 5

[0063] In Example 5, steps (1) and (2) are the same as those in Example 1;

[0064] (3) The modified activated carbon intermediate and a methanol solution of trimethoxysilane with a mass fraction of 10% were refluxed at 50° C. for 8 h, then filtered and washed with methanol, dried in an oven at 80° C. for later use, to obtain a modified activated carbon with a hydrophobic group content of 0.16 mmol / g;

[0065] (4)(5) The method of steps (4) and (5) of Example 1 was adopted to finally obtain a reduced palladium carbon catalyst recorded as 0.05Pd / G4-AC.

[0066] Example 6

[0067] In Example 6, steps (1), (2) and (3) are the same as those in Example 5;

[0068] (4) preparing a palladium chloride precursor solution with a pH value of 1.2 and a concentration of 20 g / L, taking 60 mL of deionized water and mixing it with the modified activated carbon, stirring at 30° C. and dropping 3.3 g of the precursor solution, continuing to stir for 30 min, standing and washing with deionized water until neutral, and placing in an oven at 100° C. and drying for 12 h, a palladium carbon catalyst to be reduced with a palladium loading of 0.02% (mass fraction) can be obtained;

[0069] (5) The method of step (5) of Example 5 was used to finally obtain a reduced palladium carbon catalyst, which was recorded as 0.02Pd / G4-AC.

[0070] Comparative Example 1

[0071] The steps (1), (4) and (5) of Example 1 were followed, i.e., the activated carbon carrier was not subjected to any modification treatment and was directly impregnated with the supported palladium precursor to obtain an unmodified palladium carbon catalyst, recorded as 0.05Pd / AC.

[0072] Comparative Example 2

[0073] According to steps (1), (2), (4) and (5) of Example 1, the activated carbon was oxidatively modified to introduce hydrophilic groups, and then impregnated with a palladium precursor to obtain a hydrophilically modified palladium carbon catalyst, which was recorded as 0.05Pd / G6-AC.

[0074] Comparative Example 3

[0075] According to steps (1), (3), (4) and (5) of Example 1, the activated carbon was hydrophobically modified and then impregnated with a palladium precursor to obtain a hydrophobically modified palladium carbon catalyst, recorded as 0.05Pd / G7-AC.

[0076] Catalyst Evaluation 1

[0077] The catalysts obtained in Examples 1-6 and Comparative Examples 1-3 were used in a fixed bed to hydrogenate dimethyl maleate to produce dimethyl succinate. The specific reaction conditions are shown in Table 1. The mass percentage of dimethyl maleate in the raw material used was 99.8%. The mixture after the reaction was analyzed by gas chromatography. The results after continuous reaction for 360 hours are shown in Table 1.

[0078] Table 1 Catalyst crystal size, reaction conditions and evaluation results obtained in each case

[0079]

[0080] Catalyst Evaluation 2

[0081] The catalyst obtained in Example 3 was used in a fixed bed to hydrogenate dimethyl maleate to produce dimethyl succinate. The reaction conditions were: reaction temperature of 100°C, pressure of 1 MPa, volume space velocity of 1.5 h -1 , the hydrogen-ester molar ratio is 20:1. The mass percentage of dimethyl maleate in the raw material used is 99.8%. The reaction is continued for 2000 hours, and the catalyst stability is evaluated. The mixture after the reaction is analyzed by gas chromatography, and the results are shown in Table 2.

[0082] Table 2 Evaluation results of the catalyst obtained in Example 3 after continuous reaction for 2000 h

[0083] Reaction time DMM conversion rate / % DMS selectivity / % 50 99.9 99.4 300 100 99.8 500 100 99.7 800 100 99.6 1500 100 99.6 2000 100 99.5

[0084] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A dialkyl maleate hydrogenation catalyst, characterized in that: The catalyst comprises: modified activated carbon and noble metal active components, wherein the modified activated carbon is activated carbon having hydrophilic groups dispersed by hydrophobic groups on the surface, and the size of the noble metal particles is less than 2.0 nm.

2. The catalyst according to claim 1, characterized in that: The hydrophobic group is derived from a hydrophobic modifier, which is an organic silane substance, selected from at least one of vinyl trichlorosilane, phenyl dichlorosilane, chloromethyl triethoxysilane, vinyl triethoxysilane, vinyl triacetoxysilane, trimethoxysilane, trimethoxyvinyl silane, and dimethoxymethylvinyl silane, preferably at least one of trimethoxysilane, vinyl triethoxysilane, trimethoxyvinyl silane, and dimethoxymethylvinyl silane, more preferably at least one of trimethoxyvinyl silane and dimethoxymethylvinyl silane; the amount of the hydrophobic group is 0.1 to 1 mmol / g, preferably 0.1 to 0.6 mmol / g.

3. The catalyst according to claim 1, characterized in that: The ratio of the number of the hydrophobic groups to the number of the hydrophilic groups is 0.05 to 1:1, preferably 0.1 to 0.4:

1.

4. The catalyst according to claim 1, characterized in that: The hydrophilic group is at least one of a carboxyl group, a phenolic hydroxyl group or a lactone group; the amount of the hydrophilic group is not less than 0.3 mmol / g, preferably not less than 0.5 mmol / g, and more preferably 0.5 to 1.4 mmol / g.

5. The catalyst according to claim 1, characterized in that: The noble metal is at least one of palladium, ruthenium, rhodium and platinum, preferably at least one of palladium and ruthenium, and more preferably palladium.

6. The catalyst according to claim 1, characterized in that: In the catalyst, the content of the noble metal in terms of element is 0.01% to 0.20%, preferably 0.02% to 0.10%, based on the weight of the catalyst.

7. The catalyst according to claim 1, characterized in that: In the catalyst, the size of the noble metal particles is 1.0 nm or less, preferably 0.2 to 1.0 nm.

8. A method for preparing a dialkyl maleate hydrogenation catalyst, characterized in that: include: (1) An oxidizing agent is mixed with activated carbon and treated at a temperature of 20 to 90° C. for 0.5 to 24 hours to obtain a modified activated carbon intermediate; (2) The modified activated carbon intermediate obtained in step (1) is mixed and stirred with an alcohol solution of a hydrophobic modifier at 20 to 80° C. for 4 to 24 hours, filtered, washed, and dried to obtain modified activated carbon; (3) Loading precious metal active components on the modified activated carbon obtained in step (2) to obtain the catalyst.

9. The method according to claim 8, characterized in that: In step (1), the activated carbon is derived from at least one of wood-based activated carbon, petroleum-based activated carbon, and coal-based activated carbon, wherein the wood-based activated carbon is derived from at least one of coconut shell charcoal, fruit shell charcoal, and bamboo charcoal, preferably coconut shell charcoal; the specific surface area of ​​the activated carbon used is 300 to 2000 m 2 / g, preferably 500 to 1500 m 2 / g, an average pore diameter of 0.3 to 5.0 nm, preferably 0.8 to 3.5 nm, and an ash content of no more than 10 wt%, preferably no more than 7 wt%.

10. The method according to claim 8, characterized in that: In step (1), the oxidizing agent is selected from at least one of nitric acid, hydrogen peroxide, hypochlorous acid, sodium hypochlorite, perchloric acid, sodium perchlorate, and ammonium persulfate; and the mass concentration of the oxidizing agent is 1% to 40%.

11. The method according to claim 8, characterized in that: After the treatment in step (1), the surface of the modified activated carbon intermediate has at least one of carboxyl, phenolic hydroxyl or lactone hydrophilic groups; the number of hydrophilic groups is not less than 0.3 mmol / g, preferably the number of hydrophilic groups is not less than 0.5 mmol / g, and more preferably 0.5 to 1.4 mmol / g.

12. The method according to claim 8, characterized in that: In step (2), the alcohol used in the alcohol solution is a small molecule alcohol, the carbon number of the small molecule alcohol is C1-C6, and is preferably methanol; in the alcohol solution of the hydrophobic modifier, the mass content of the hydrophobic modifier is 1% to 80%, preferably 3% to 50%, and more preferably 5% to 20%.

13. The method according to claim 8, characterized in that: In step (2), the hydrophobic modifier is an organosilane substance, selected from at least one of vinyl trichlorosilane, phenyl dichlorosilane, chloromethyl triethoxysilane, vinyl triethoxysilane, vinyl triacetoxysilane, trimethoxysilane, trimethoxyvinyl silane, and dimethoxymethyl vinyl silane, preferably at least one of trimethoxysilane, vinyl triethoxysilane, trimethoxyvinyl silane, and dimethoxymethyl vinyl silane, and more preferably at least one of trimethoxyvinyl silane and dimethoxymethyl vinyl silane.

14. The method according to claim 8, characterized in that: In step (2), the liquid-to-solid volume ratio of the alcohol solution of the hydrophobic modifier to the modified activated carbon intermediate obtained in step (1) is 3 to 10:

1.

15. The method according to claim 8, characterized in that: In step (2), the drying conditions are as follows: the drying temperature is 50 to 150° C., preferably 80 to 120° C., and the drying time is 1 to 24 hours, preferably 2 to 12 hours.

16. The method according to claim 8, characterized in that: In the modified activated carbon, the amount of hydrophobic groups is 0.1 to 1 mmol / g, preferably 0.1 to 0.6 mmol / g.

17. The method according to claim 8, characterized in that: In step (3), the method for loading the precious metal active component is as follows: the modified activated carbon is mixed with water having a saturated water absorption capacity of 2 to 5 times that of the modified activated carbon, the precious metal precursor solution is dripped into the resulting mixture under stirring conditions, and then stirring is continued for more than 15 minutes, and then allowed to stand, filtered, washed, and dried to obtain the catalyst.

18. The method according to claim 8 or 17, characterized in that: The noble metal is at least one of palladium, ruthenium, rhodium and platinum, preferably at least one of palladium and ruthenium, and more preferably palladium; in the catalyst, the content of the noble metal as an element is 0.01% to 0.20%, preferably 0.05% to 0.10%, based on the weight of the catalyst.

19. The method according to claim 8, characterized in that: In the catalyst, the size of the noble metal particles is less than 2.0 nm, preferably less than 1.0 nm, and more preferably 0.2 to 1.0 nm.

20. Use of the catalyst according to any one of claims 1 to 7 or the catalyst prepared according to any one of claims 8 to 19 in the selective hydrogenation of dialkyl maleate to prepare dialkyl succinate.

Citation Information

Patent Citations

  • Catalyst for preparing succinic acid dialkyl ester and preparation method thereof

    CN101745396A

  • Method for preparing succinic acid dialkyl ester by maleic acid dialkyl ester hydrogenation

    CN101747189A

  • Method for preparing hydrogenation catalyst for producing dimethyl succinate

    CN103464153A

  • Method for producing 1,4-butanediol by hydrogenation of dialkyl maleate in a mixed liquid / gas phase

    CN103946201B

  • An acid-resistant hydrogenation catalyst, its preparation method and application

    CN111330581B

Cited By

  • Catalyst for preparing gamma-butyrolactone through maleic anhydride hydrogenation by using alumina ceramic as support, preparation method and application

    CN120754871A

  • A catalyst for preparing gamma-butyrolactone by hydrogenating maleic anhydride supported by alumina ceramic, a preparation method and application thereof

    CN120754871B